The Strait of Malacca, The Focus of Cultural Acculturation of Four Regions (South Asia, East Asia, West Asia and Southeast Asia): Selat Malaka, Titik Tumpu Akulturasi Budaya Empat Kawasan (Asia Selatan, Asia Timur, Asia Barat dan Asia Tenggara) - Fauwaz, Aisyah; Diyanto, Rahman (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2025)
The various nations that came to the Strait of Malacca brought with them diverse cultures as a trading hub, giving rise to a fusion of the cultures of the immigrants and the native population. Consequently, ongoing activities led to a blending of these cultures, which over time formed new cultures, especially in the surrounding regions. The Strait of Malacca's long-standing reputation as an international trade route is indeed unwavering. However, if the Strait of Malacca is read as a focal point for cultural mixing across three regions, it will undoubtedly give rise to incidents. A qualitative approach is an ideal method for developing research that begins with a hypothesis. This study begins with the tentative hypothesis that the Strait of Malacca may indeed be a focal point for cultural acculturation. Sources and data from various literature then serve as the data collection method in this study. This study aims to find the precise reasons why the Strait of Malacca deserves to be called a focal point for cultural acculturation from various regions, especially Asia (Central, East, West and Southeast). The results obtained indicate that the Strait of Malacca is indeed worthy of the status of an area that supports the mixing or acculturation of cultures throughout the world, especially in these three regions. This is proven by the cultures, especially those in Southeast Asia today, which are the result of cultural acculturation, where the original culture of sailors and traders has mixed with the culture of each ethnic group that flows into the Strait of Malacca.